Synthesis and Characterization of Bed Adsorbent from Coconut Shell for Separation of CO2 from Natural Gas - Ng, Jia Ping (Universiti Teknologi PETRONAS, 2016)
Biomass wastes are considered as sustainable carbon precursor which can be used in synthesizing activated carbon. A series of activated carbon will be prepared by using biomass waste which is coconut shell. This activated carbon will be activated thermally and chemically. All the activated carbon samples will be activated chemically using chemical reagent sodium hydroxide (NaOH). Different concentration and loading of the chemical will be used in activation as well as different retention time in order to observe and determine the optimum activation condition for better adsorption performance. It is found out that mass ratio of 2:1 shows the highest CO2 adsorption capacity which is 1.5253mmol/g. Porosity of the activated carbon increases with the increasing mass ratio and increasing activation temperature.